2020
DOI: 10.1111/jch.13928
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and the prevalence of hypertension in Chinese adults: The Dongfeng‐Tongji cohort

Abstract: Although many studies explored the association between helicobacter pylori (H pylori) infection and hypertension, there is no consensus. This study is to investigate the association between H pylori infection and the prevalence of hypertension among a middle‐ and old‐age Chinese population. A cross‐sectional study including 17,100 participants from the Dongfeng‐Tongji cohort study was performed. All participants underwent a 14C‐urea breath test and a routine health check‐up. Logistics and linear regression wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 27 publications
2
34
1
Order By: Relevance
“…pylori infection and hypertension in Chinese adults, which presumably resulted from atherosclerosis induced by H . pylori -related pro-inflammatory cytokines [ 22 ]. Lastly, the most important risk factor for the development of IM was current H .…”
Section: Discussionmentioning
confidence: 99%
“…pylori infection and hypertension in Chinese adults, which presumably resulted from atherosclerosis induced by H . pylori -related pro-inflammatory cytokines [ 22 ]. Lastly, the most important risk factor for the development of IM was current H .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the immunocompromised status after transplantation and the high prevalence of H. pylori infection among the general population in China (50%), the risk of H. pylori recurrence among LT recipients may be significantly elevated compared with the general population. In addition, a significant proportion of LT recipients have metabolic syndrome, which may also increase the likelihood of H. pylori re‐infection 22,23 . Therefore, screening and treating infected family members and improving sanitary conditions are recommended to reduce the risk of H. pylori recurrence in LT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a significant proportion of LT recipients have metabolic syndrome, which may also increase the likelihood of H. pylori re-infection. 22,23 Therefore, screening and treating infected family members and improving sanitary conditions are recommended to reduce the risk of H. pylori recurrence in LT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for traditional CVD risk factors, H. pylori infection is found to be the only independent predictor of incident carotid plaque with the multivariate odds ratio (OR) of 2.3, and incident acute stroke (with multivariate OR of 3.6) [31]. H. pylori infection was positively associated with the prevalence of HTN among Chinese adults [25,26].…”
Section: Brief Overview On H Pylori Infection and Cardiovascular Diseasesmentioning
confidence: 96%
“…A recent meta-analysis with a large population showed that H. pylori infection increased the risk of adverse cardiovascular events by 51%, mostly due to myocardial infarction and cerebrovascular disease [23]. Data also suggests that H. pylori infection increases the risk of coronary heart diseases (CHD) and related events predominantly in a patient's early life [24], and is positively associated with HTN [25,26]. In this chapter, efforts will be focused on: 1) brief overview on the association of H. pylori infection and CVDs; 2) relationship between H. pylori infection and atherosclerosis; 3) H. pylori infection and endothelial dysfunction; 4) role of exosomes in mediating the effect of H. pylori infection on endothelial function, and 5) significance and clinical implications.…”
Section: Introductionmentioning
confidence: 99%